Development of an ATTiny1614-Based Heater Controller and a Silicone-Based Heating Element for a Tissue Processor - Hendry, Jans; Isnianto, Hidayat Nur; Hudati, Imroatul; Irsyadi, Fakih; Najib, Muhammad; Fauzi, Ilham (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2025)
The tissue processor is an essential device for preparing tissue samples for observation. Despite the high demand, no similar products havebeen developed locally. Therefore, the researchers have undertaken the development of a comparable device through reverse engineering. One of the key components of a tissue processor is the automatic heater, which consists of a heater controller and a heating element. Utilizing an ATTiny1614 microcontroller and a silicone pad, both components were developed to operate with the same functionality as the original. Based on the tests, the heater controller successfully supplied alternating current to the heating element according to the specified maximum temperature. The heating element test showed an impedance specification of 418.9 Ω and required only approximately 1 minute and 37 seconds to reach a temperature of 100 °C. Therefore, the resulting prototype meets the criteria for an automatic heater for a tissue processor.